2017
DOI: 10.2147/nds.s129891
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol-rich mixture inhibits cell proliferation and induces apoptosis via down-regulation of the Notch-1/NF-κB pathways in NSCLC cells

Abstract: Abstract:Lung cancer is one of the leading causes of cancer deaths. Non-small cell lung cancer (NSCLC), with a 5-year survival rate of 5% at stage IIIB, accounts for 80%-85% of all lung cancers. Aberrant Notch-1 expressions have been reported in lung cancer patients and could potentially be a beneficial molecular/therapeutic target against NSCLC. Tocotrienols, isomers of vitamin E, have been shown to exhibit antitumor activity via inhibition of different signaling pathways in tumor cells. Previously, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…Notch-1 has been targeted in several such studies leading to promising results. A tocotrienol mixture reduced its levels in a dose-dependent manner, led to apoptosis and inhibited cell growth and invasiveness [51]. Similarly, the analogue delta-tocotrienol decreased the expression of Notch-1 and its downstream genes, led to G0-G1 cell arrest and decreased their invasive capability three-fold compared to controls [69].…”
Section: Pharmacological Targetingmentioning
confidence: 98%
See 1 more Smart Citation
“…Notch-1 has been targeted in several such studies leading to promising results. A tocotrienol mixture reduced its levels in a dose-dependent manner, led to apoptosis and inhibited cell growth and invasiveness [51]. Similarly, the analogue delta-tocotrienol decreased the expression of Notch-1 and its downstream genes, led to G0-G1 cell arrest and decreased their invasive capability three-fold compared to controls [69].…”
Section: Pharmacological Targetingmentioning
confidence: 98%
“…Once translocated, NICD forms a transcription complex with other TFs and activates genes of the Hes and Hey families as well as VEGF, NFkB, BcL family members, c-myc, Ras and cyclin D1 [47,48,50]. In total, there are four different variants of the Notch receptor: Notch-1, Notch-2, Notch-3 and Notch-4, all of which have different functions in NSCLC [51]. Furthermore, there are two Jagged ligand variants, JAG1 and JAG2, as well as three Delta-like ligand (DLLs) variants: DLL1, DLL3 and DLL4 [52,53].…”
Section: Pathway Descriptionmentioning
confidence: 99%
“…γ-T3 acted as an effective inducer of apoptosis in K562 chronic myeloid leukemia cells, which was mediated by both extrinsic and intrinsic apoptotic pathways [57]. Rajasinghe and Gupta showed that tocotrienol-rich mixture hindered cell proliferation, migration, and tumor cell invasiveness by downregulating NF-κB and Notch-1 pathways during apoptosis induction in non-small cell lung cancer cells (NSCLC) [58]. In 2017, Xu et al, concluded that γ-T3 acted as anti-proliferative agent and induced apoptosis in HeLa cells via the mitochondrial pathway [59].…”
Section: Major Anti-cancer Functions Of Tocotrienolsmentioning
confidence: 99%
“…δ and γ-T3 were also reported to suppress Ras-Raf-MEK-ERK pathway-associated upstream signaling, which in turn can inhibit angiogenesis and proliferation in human hepatocellular carcinoma (HepG2) cells [82]. Rajasinghe and colleagues in 2017 reported the bioactive potential of tocotrienol rich mixture in inhibiting proliferation in lung adenocarcinoma (A549) and squamous cell lung cancer (H520) cell lines via downregulation of NF-κB and downstream pro-angiogenic molecules (Figure 4) [58]. In another study carried out by Husain and colleagues, it was demonstrated that δ-T3 inhibited biomarkers of tumor angiogenesis (VEGF and MMP-9) in pancreatic cancer cells (L3.6pl and MiaPaCa-2) in vitro and decreased the expression of CSCs cell surface markers (CD31 and CD44) [83].…”
Section: Major Anti-cancer Functions Of Tocotrienolsmentioning
confidence: 99%
“…Inhibition of NF-κB by tocotrienols has been reported to reduce the expression of various proteins linked to cell survival, such as antiapoptosis (e.g., Bcl-2, Bcl-xL, cFLIP, IAP-1, IAP-2, XIAP, Bfl-1/A1, TRAF1, and survivin), proliferation (e.g., c-Myc and cyclin D1), inflammation (COX-2, cytokines), invasion (e.g., MMP-9, ICAM-1, ELAM-1, and VCAM-1), and neoangiogenesis (e.g., VEGF) [92,93,94]. Tocotrienols have been shown to reduce constitutive NF-κB activity in mammary epithelial [95], prostate cancer [19], multiple myeloma [92], lung adenocarcinoma [96], oral cancer [97], and colon carcinoma [56] cell lines. A study conducted on pancreatic cancer showed that γ-T3 was able to suppress NF-κB activity in vitro and in vivo [98].…”
Section: Tocotrienols Target Prosurvival Signaling Pathwaysmentioning
confidence: 99%